Saint young men. 2 - Nakamura, Hikaru, 1984- (Kodansha Comics, 2020)
Buddha, the Enlightened One, and Jesus, Son of God, continue their goofy adventures through modern-day Tokyo, with escha-pades aplenty. The wise guys of Tachikawa, along with their band of saintly companions and immortal foes, immerse themselves even deeper into daily life among their new neighborhood acquaintances. As the seasons turn, new adventures await them around every corner: from the blissful highs of bullet train travel and gaming with friends to the mundane challenges of staying on budget when you have to pay for rent and groceries, not to mention Valentine's chocolates when you are filled with love for all of humankind ...